Extraordinarily stable and wide‐temperature range sodium/potassium‐ion batteries based on 1D SnSe2‐SePAN composite nanofibers - Yiyi Wang; Fuyu Xiao; Xi Chen; Peixun Xiong; Chuyuan Lin; Hong‐En Wang; Mingdeng Wei; Qingrong Qian; Qinghua Chen; Lingxing Zeng (InfoMat, 2023)
Abstract Developing electrodes with long lifespan and wide‐temperature adaptability is crucial important to achieve high‐performance sodium/potassium‐ion batteries (SIBs/PIBs). Herein, the SnSe2‐SePAN composite was fabricated for extraordinarily stable and wide‐temperature range SIBs/PIBs through a coupling strategy between controllable electrospinning and selenylation, in which SnSe2 nanoparticles were uniformly encapsulated in the SePAN matrix. The unique structure of SnSe2‐SePAN not only relieves drastic volume variation but also guarantees the structural integrity of the composite, endowing SnSe2‐SePAN with excellent sodium/potassium storage properties. Consequently, SnSe2‐SePAN displays a high sodium storage capacity and excellent feasibility in a wide working temperature range (−15 to 60°C: 300 mAh g−1/700 cycles/−15°C; 352 mAh g−1/100 cycles/60°C at 0.5 A g−1). At room temperature, it delivers a record‐ultralong cycling life of 192 mAh g−1 that exceeds 66 000 cycles even at 15 A g−1. It exhibits extremely superb electrochemical performance in PIBs (157 mAh g−1 exceeding 15 000 cycles at 5 A g−1). The ex situ XRD and TEM results attest the conversion‐alloy mechanism of SnSe2‐SePAN. Also, computational calculations verify that SePAN takes an important role in intensifying the electrochemical performance of SnSe2‐SePAN electrode. Therefore, this study breaks new ground on solving the polyselenide dissolution issue and improving the wide temperature workable performance of sodium/potassium storage.